Fostering metacognitive skill: A means to improve students’ academic achievement - Andini Maulida Rizkia; Zulfiani Zulfiani (Biosfer: Jurnal Pendidikan Biologi, 2021)
Metacognition is one of the five key learning skills in the 21st century. This research aims to describe the profile of the students' metacognitive skills in biology learning at Tangerang Selatan Senior High School. This type of research was survey with descriptive approach. The population of this research was students of Senior High school in Tangerang Selatan, Indonesia. Sampling was conducted with stratified sampling, four school was determined by random sampling. Data on metacognitive skills are collected using questionnaires with supporting data in the form of interviews, observations, and documentation. The survey results of metacognitive skills and observation were analyzed using descriptive statistics. Based on the results of the survey, the average planning result is 72.47%, monitoring by 73%, and evaluating by 72.17%. The results showed that students' metacognitive skills in biology are in a strong category so that these skills can support the increase learner academic outcomes in the learning process.